Exploring principal development and teacher outcomes : how principals can strengthen instruction, teacher retention, and student achievement - Youngs, Peter; Kim, Jihyun (College teacher in education); Mavrogordato, Madeline Emily Clark (New York : Routledge, 2021)
"This edited volume examines innovative ways of preparing, supervising, and evaluating principals and explores factors that promote effective leadership practices. Chapter authors consider how principals' leadership practices affect teachers' instruction, satisfaction, commitment, retention, and effectiveness, and present evidence that principals can influence key student outcomes as well. Covering topics such as school leaders' use of time, their efforts to reduce implicit bias, how leadership practices are associated with teachers' workplace attitudes, leadership and student achievement, and how school leaders can best be supported under new federal legislation, this volume is a "must read" for educational leadership and policy faculty, school and district administrators, and researchers committed to promoting effective principal leadership"--
Introduction -- Section 1. Principal Development and Evaluation. Growing your own leadership pipeline: The case of an urban school leadership residency -- Preparing educational leaders for adaptive leadership -- Changing principal supervision to develop principals' instructional leadership capacity -- Appraising principal evaluation and development: Current research and future directions -- Section 2. Principal Leadership Practices. Examining the time principals dedicate to interacting with teachers and other educational stakeholders -- Equity endeavors through the justice for bias framework: Principals addressing implicit bias in schools -- Using social network analysis to support improvement science approaches in education -- Section 3. Principal Leadership Practices and Teacher and Student Outcomes. Principal leadership and beginning elementary teachers' self-efficacy and valuing of ambitious instructional practices -- Improving instruction for students with disabilities: A call for effective principal leadership -- Principal leadership activities and teachers' workplace attitudes -- How principal leadership and teacher burnout are associated with early career teacher mobility: Insights from the beginning teacher longitudinal survey -- Principal leadership practices, organizational improvement, and student achievement -- Section 4. Next Steps for Leadership Practice and Research. How states use ESSA to support principal preparation, development, and quality -- Exploring principal development and teacher outcomes: Lessons learned and guidelines for practice.
Includes bibliographical references and index.
Keywords: School principals -- In-service training; Educational leadership; Teacher-principal relationships